The effectiveness of blood flow restriction training in optimizing physiological indicators in elite female handball players - Tyshchenko, D.; Diachenko, M.; Tyshchenko, V.; Sokolova, O.; Veritov, O.; Bubela, O.-O.; Atamanyuk, S.; Todorova, V. (Journal of Physical Education and Sport, 2025)
This study explored the effectiveness of blood flow restriction (BFR) training methods as an innovative strategy for enhancing the physical fitness of elite female handball players. The research was aimed to evaluate thoroughly the efficacy of BFR-training as a tool for optimizing the physical characteristics of these athletes. Material and methods. The study involved 26 elite female athletes from the "Halychanka" women's handball club, selected based on specific criteria such as age, athletic experience, and performance level. A longitudinal, comparative design was used to assess the effects of different training programs on athletes' performance. The participants were divided into the control group and the experimental group. The study lasted within 8 weeks, during which both groups underwent a standard training program aimed at improving strength, speed and endurance performance. The experimental group additionally performed blood flow restriction exercise twice a week to develop explosive power, leg strength, and endurance. The control group performed normal strength exercises without BFR. Testing methods included repeated jump tests, Yo-Yo tests, grip strength assessments, with statistical analyses performed to evaluate pre- and post-training results. Results. The experimental group showed statistically significant improvements in explosive power, throwing accuracy, speed, and endurance compared to the control group. Enhanced muscle activation and increased levels of growth hormone (GH) and insulin-like growth factor-1 (IGF-1) were observed, contributing to muscle hypertrophy and faster recovery. Additionally, metabolic stress from BFR led to adaptations in anaerobic and aerobic systems, enhancing overall physical performance. Discussion. The results of the study supported existing evidence on the efficacy of BFR training for promoting neuromuscular adaptations and metabolic efficiency. The low-load approach reduced strain on joints while stimulating fast-twitch muscle fibers, crucial for explosive movements in handball. BFR training demonstrated significant potential for injury prevention and performance optimization in high-demand sports. Conclusions. The obtained results confirmed that the implementation of BFR training was an effective mean to improve the physical qualities which are necessary for successful performance in handball and reduces the risk of injuries due to the use of lower loads. It was recommended to integrate BFR training into the training process of handball players to achieve optimal sports results.